Case report: Surgical valvular pulmonary reconstruction for a previous unreported rheumatic right-sided valve disease with severe pulmonary regurgitation - Zhou, Zijing; Tang, Weijie; Tu, Xiaokang; Li, Feng; Huang, Zhonghua; Jin, Wancun; Wu, Qin; Liu, Feng; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2023)
Rheumatic heart disease (RHD) is a widespread illness in developing countries. RHD causes 99% of mitral stenoses in adults and 25% of aortic regurgitation. However, it only causes 10% of stenoses of the tricuspid valve, and is almost always associated with left-side valvular lesions. Isolated right-side valves are rarely affected, but may result in severe rheumatic pulmonary regurgitation. Herein, we present a case of rheumatic right-sided valve disease with severe pulmonary valve contracture and regurgitation in a symptomatic patient, successfully managed by surgical valvular reconstruction with a tailored bileaflet bovine pericardial patch. The options for surgical approach are also discussed. To our knowledge, the presented rheumatic right-sided valve disease with severe pulmonary regurgitation is the first to be reported in the literature.